Formative Speaking Assessment and Its Role in Supporting EFL Students’ Learning - Sunoko Setyawan; Titik Rahayu; Nara Sari (Jurnal Pendidikan Bahasa Inggris Undiksha, 2026)
This study aimed to explore formative speaking assessment practices and their role in supporting EFL students’ learning in a Speaking for Instructional Purpose course. A qualitative descriptive research design was employed and conducted with third-semester undergraduate students in an English Education program at a public university in Indonesia. Data were collected through classroom observations, document analysis, and an open-ended student questionnaire. Classroom observations were used to examine how formative speaking assessment was integrated into instructional activities, while document analysis focused on assessment criteria and feedback practices. The questionnaire was administered to capture students’ perceptions of how formative assessment supported their learning. The data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that formative speaking assessment was systematically embedded in speaking instructional activities and functioned as a learning-supportive process rather than merely an evaluative tool. Improvement-oriented feedback helped students understand speaking expectations, reflect on their performance, and actively engage in learning activities. In addition, formative assessment contributed to increased confidence and participation in speaking tasks. These findings indicate that formative speaking assessment plays a significant role in supporting EFL students’ learning processes when it is closely aligned with instructional goals